2008
DOI: 10.1111/j.1552-6569.2007.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Lymphoma Characterization by Diffusion‐Weighted Imaging and MR Spectroscopy

Abstract: Restricted diffusion is a consistent imaging finding in CNS lymphoma in immunocompetent patients. Spectroscopy is helpful in initial imaging diagnosis and post-treatment surveillance. These lesions are usually paraventricular in location. MR imaging appearances differ among immunocompetent and immunosuppressed individuals in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
95
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 27 publications
(65 reference statements)
9
95
0
3
Order By: Relevance
“…In our study, we did not observe a clear tendency in DWI, although in immunocompetent patients, twice as many lesions were restricted than in immunodeficient patients (perhaps due to the high percentage of necrosis). This is similar to some other studies showing high rates of restricted diffusion in immunocompetent patients [30] . We must consider, especially in immunodeficient patients, that in lesions with peripheral enhancement and central necrosis, abscesses should be included in the differential diagnosis, as they have a typical restricted pattern in DWI [19] .…”
Section: Mri Featuressupporting
confidence: 80%
“…In our study, we did not observe a clear tendency in DWI, although in immunocompetent patients, twice as many lesions were restricted than in immunodeficient patients (perhaps due to the high percentage of necrosis). This is similar to some other studies showing high rates of restricted diffusion in immunocompetent patients [30] . We must consider, especially in immunodeficient patients, that in lesions with peripheral enhancement and central necrosis, abscesses should be included in the differential diagnosis, as they have a typical restricted pattern in DWI [19] .…”
Section: Mri Featuressupporting
confidence: 80%
“…Cerebral edema is usually larger than the area of contrast enhancement and is thus responsible for the apparent mass effect. The diffusion weighted scans are consistent with the increased diffusivity of water protons [4]. Even if these MRI features of PCNSL are recognized, differentiating it from other diagnoses -including malignant gliomas, metastases, and inflammatory disorders-is not always easy [5].…”
Section: Introductionmentioning
confidence: 55%
“…A high lipid peak in PCNSLs and a variable lip-lac peak in patients with TDL have been previously noted by many other researchers. 1,3,10,15,16 In our study, we classified the lip-lac grade by visual judgment, which could easily be applied in daily clinical practice. We found that a high-grade lip-lac (grade Ͼ3) was mostly shown in PCNSLs regardless of whether there was necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Their incidence has been increasing during the past 2 decades not only in immunocompromised patients but also in immunocompetent patients. 2,3 Typical MR imaging features of PCNSLs are characterized by their periventricular locations, well-defined margin, moderate or marked edema, and intense and homogeneous nodular enhancement and are usually easy to correctly diagnose. [4][5][6] However, some patients present with atypical MR imaging features, commonly those of heterogeneous enhancement, such as patchy enhancement, streaky enhancement without mass formation, or even no enhancement.…”
mentioning
confidence: 99%